Upaya Guru BK dalam Menangani Kenakalan Remaja/Siswa di MTSN 4 Bajubang - Sherlyamelia (Pedagogika: Jurnal Ilmu-Ilmu Kependidikan, 2021)
This research was carried out in Bajubang, more precisely at MTS N 4 BAJUBANG, Bajubang District. The problems studied are; How do teachers deal with juvenile delinquency that occurred at MTS 4 Bajubang; what are the factors that cause juvenile delinquency and; what is the form of juvenile delinquency in MTS N 4 Bajubang; the impact of juvenile delinquency for the perpetrators, this study aims to find out what are the factors causing juvenile delinquency/violations that exist in MTS N 4 Bajubang and how BK teachers handle cases or violations that occur in MTS N 4 Bajubang, this study uses the interview method with Some questions were asked to the BK teacher at MTS N 4 Bajubang who was the resource person: Jihan Indah Alqarani. From this study, juvenile delinquency or violations committed at MTS N 4 Bajubang, among others. skipping, smoking, carrying cellphones, bullying and watching adult videos. The delinquency was carried out with full awareness among them because of curiosity and this delinquency was sanctioned by the school.